Epidemiological aspects of tuberculosis / HIV coinfection: a decade-long analysis in Teresina, Piauí, Brazil (Research, Society and Development, 2020)
Tuberculosis (TB) is a worldwide public health problem that has worsened over the past three decades. TB / HIV co-infection is responsible for the increase in incidence, prevalence and mortality, as well as the increase in multidrug resistance to drugs used to treat the disease. This work aims to analyze epidemiological aspects of Tuberculosis / HIV co-infection in the city of Teresina-PI from 2009 to 2018 obtained in the Information System for Notifiable Diseases (SINAN). This is a retrospective and descriptive epidemiological study of a population nature, in which secondary data from cases of patients with tuberculosis / HIV coinfection in the city of Teresina-PI were used, evaluating aspects related to sex, age group, race, education, evolution and clinical forms, number of cases in the municipality and clinical evolution of the disease. The data were exported and analyzed using the Microsoft Office Excel 2016 program. The individuals most affected by the disease are male, aged between 25 and 34 years. The predominant race is the indigenous brown. Regarding the year with the highest incidence of confirmed cases, 2012 (14.57%) appears in first place. Regarding schooling criteria, 4th to 8th incomplete grades of elementary school were prevalent. It is noted that the most recurrent clinical evolution was hospital discharge / cure.